Two competitive ignition mechanism for dynamic extrusion-shear loaded high-energy propellant - Dong, Liying; Wu, Yanqing; Yang, Kun; Zhu, Junwu; Wu, Xingzhong (Mechanics of materials, 2025)
Tactical missiles frequently experience accidental drops, impacts, and other events during maintenance and battlefield operations, subjecting their internal high-energy propellants to complex loads like extrusion-shear, which can trigger ignition and pose safety hazards. This study aims to elucidate the ignition mechanism of high-energy propellants under extrusion-shear and establish a predictive method. Firstly, a visualized extrusion-shear experiment was designed to directly observe the whole process of deformation, damage and ignition of GRT propellant. By adjusting the gap size, the correlation between overall flow deformation and local ignition mechanisms was explored. Secondly, a thermo-mechanical coupling model and a macro-micro perspective ignition criterion were integrated into the LS-DYNA subroutine to simulate local ignition responses under extrusion-shear loading and compare them with other ignition criteria. The results show that the fracture surface extending from the gap divides the sample into flow and stagnant regions, forming a slip surface at the boundary. As the gap size decreases from Φ3 × 23 mm to Φ1 × 1 mm, the ignition mechanism transitions from viscous external friction to viscous internal friction, altering the viscous frictional heating rate and resulting in distinct threshold velocities. The macro-micro-scale ignition criterion based on the viscous internal friction mechanism effectively describes the ignition behavior of GRT propellant under narrow gaps, and compared to other ignition criteria, provides the closest match with experimental results, demonstrating excellent universality. •A novel visual dynamic extrusion-shear test device was developed to observe the deformation, damage, and ignition responses of GRT propellant materials. It qualitatively identifies primary ignition mechanisms at macro-micro-scales and examines the influence of gap size on their competition.•A coupled thermo-mechanical model is embedded into the LS-DYNA subroutine, providing quantitative evidence for the ignition dominant mechanism.